Cyclic lateral load behavior of squat reinforced concrete walls. (1st April 2018) - Terzioglu, Tevfik; Orakcal, Kutay; Massone, Leonardo M.
Highlights: Experimental lateral load behavior of shear-controlled reinforced concrete squat walls. Abstract: The level of existing research, as well as current code provisions and modeling approaches, are not adequate to characterize the behavior of squat reinforced concrete walls with shear – controlled responses. In this study, an experimental program was conducted to investigate the shear-dominated response attributes of eleven squat wall specimens; including their failure mode, lateral load capacity, ductility, hysteretic response characteristics, and deformation characteristics. Test parameters included the wall aspect ratio, the amounts of vertical and horizontal web reinforcement and longitudinal boundary reinforcement, and the level of axial load. The experimental findings are presented and discussed in this paper, with emphasis on the observed failure mode, shear strength, deformation capacity, and strength degradation characteristics of the walls tested, as well as the contribution of shear, flexural, and sliding deformations to wall lateral displacements. Comparison of the test results with backbone curves specified in performance assessment guidelines is also provided.